(untitled) (Journal of actual problems of jurisprudence, 2019)
This paper addresses issues relating to the lack of regulatory mechanism for calculating the term of the licence validity; the presence of non-uniform rules in relation to the term of the licence validity in the fuel and energy complex in Ukraine. The author has provided definitions of the term of the licence validity and proposed procedures for calculating the term of the licence validity, namely in the fuel and energy complex in Ukraine. Key words: term, time, term of the licence validity, the beginning of the term of the licence validity, area of the fuel and energy complex in Ukraine.